The distribution of null case and pro in Mah Meri phrases / Shazlin Niza Ab Razak - Shazlin Niza, Ab Razak (2016)
This dissertation analyses the existence of Null Case and PRO within the Mah Meri language following the Minimalist approach by Noam Chomsky who argues that PRO has null case checked by non-finite ‘T’. The Mah Meri language being one of the endangered languages is dying since it is spoken only by most adults within the population and not practiced among the children. Due to that, this research can contribute to the documentation of Mah Meri language in syntax. In addition to that, like any other languages, the non-finite phrases of the Mah Meri language will be identified to analyses the PRO as null case suggested by the Minimalist Approach. Findings reveal that in the Null Subject Parameter, there are Null Case and PRO existence in Mah Meri phrases.